Targeting Insulin Receptor with a Novel Internalizing Aptamer - Margherita Iaboni; Raffaela Fontanella; Anna Rienzo; Maria Capuozzo; Silvia Nuzzo; Gianluca Santamaria; Silvia Catuogno; Gerolama Condorelli; Vittorio de Franciscis; Carla Lucia Esposito (Elsevier, 2016)
Nucleic acid-based aptamers are emerging as therapeutic antagonists of disease-associated proteins such as receptor tyrosine kinases. They are selected by an in vitro combinatorial chemistry approach, named Systematic Evolution of Ligands by Exponential enrichment (SELEX), and thanks to their small size and unique chemical characteristics, they possess several advantages over antibodies as diagnostics and therapeutics. In addition, aptamers that rapidly internalize into target cells hold as well great potential for their in vivo use as delivery tools of secondary therapeutic agents. Here, we describe a nuclease resistant RNA aptamer, named GL56, which specifically recognizes the insulin receptor (IR). Isolated by a cell-based SELEX method that allows enrichment for internalizing aptamers, GL56 rapidly internalizes into target cells and is able to discriminate IR from the highly homologous insulin-like growth factor receptor 1. Notably, when applied to IR expressing cancer cells, the aptamer inhibits IR dependent signaling. Given the growing interest in the insulin receptor as target for cancer treatment, GL56 reveals a novel molecule with great translational potential as inhibitor and delivery tool for IR-dependent cancers.